2022
DOI: 10.1155/2022/5447017
|View full text |Cite
|
Sign up to set email alerts
|

Pancancer Analysis of Revealed TDO2 as a Biomarker of Prognosis and Immunotherapy

Abstract: Background. Tryptophan 2,3-dioxygenase (TDO) encoded by TDO2, a rate-limiting enzyme in the kynurenine pathway, catabolizes tryptophan to kynurenine, evades immune surveillance, and promotes tumor growth. Although accumulating evidence suggests a crucial role of TDO2 during tumor formation and development, systematic evaluation of TDO2 across human cancers has rarely been reported. Methods. To shed more light on the role of TDO2 in human cancer, we explored the expression profiles of TDO2 and identified its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…To further screen for differential cell types in OS, the abundance of eight cell types in OS and normal tissues from the GSE36001 dataset was analyzed using the CIBERSORT algorithm (Figure 2A). Studies show that immune checkpoints TDO2, PDCD1, LGALS9, and PVR play an important role in cancer treatment and prognosis (Stamm et al, 2018;Fan et al, 2020;Miao et al, 2020;Cui et al, 2022). Based on Pearson correlation analysis, cell abundance was screened to be significantly correlated with immune checkpoint expression levels, and the results showed that the abundance of B cells, cancer-associated fibroblasts (CAFs), endothelial cells, and plasmocytes were significantly correlated with immune checkpoints TDO2 (p = .043), PDCD1 (p = .017), LGALS9 (p = .017), and PVR (p = .026), respectively (Figure 2B).…”
Section: Collection Of Differential Cell Typesmentioning
confidence: 99%
“…To further screen for differential cell types in OS, the abundance of eight cell types in OS and normal tissues from the GSE36001 dataset was analyzed using the CIBERSORT algorithm (Figure 2A). Studies show that immune checkpoints TDO2, PDCD1, LGALS9, and PVR play an important role in cancer treatment and prognosis (Stamm et al, 2018;Fan et al, 2020;Miao et al, 2020;Cui et al, 2022). Based on Pearson correlation analysis, cell abundance was screened to be significantly correlated with immune checkpoint expression levels, and the results showed that the abundance of B cells, cancer-associated fibroblasts (CAFs), endothelial cells, and plasmocytes were significantly correlated with immune checkpoints TDO2 (p = .043), PDCD1 (p = .017), LGALS9 (p = .017), and PVR (p = .026), respectively (Figure 2B).…”
Section: Collection Of Differential Cell Typesmentioning
confidence: 99%
“…Liver-associated tryptophan 2,3-dioxygenase (TDO2) is another heme-containing enzyme that is involved in the catabolism of Trp to downstream kynurenines ( Figure 1 ) and that has been reported to be frequently overexpressed in various malignancies ( 58 ). Elevated tumoral TDO2 expression is associated with poor prognosis in several cancer types including kidney renal papillary cell carcinoma, glioma, testicular germ cell tumors, and uveal melanoma ( 58 ) as well as liver ( 59 ), colorectal (CRC) ( 60 ), and breast cancer ( 61 ). Moreover, high TDO2 expression level positively correlated with higher immune infiltration, especially DCs, as well as immune checkpoint-related gene markers, such as LAIR1, CD276, NRP1, CD80, and CD86 ( 58 ).…”
Section: Role Of the Kynurenine Pathway In Cancer Development And Imm...mentioning
confidence: 99%
“…Elevated tumoral TDO2 expression is associated with poor prognosis in several cancer types including kidney renal papillary cell carcinoma, glioma, testicular germ cell tumors, and uveal melanoma ( 58 ) as well as liver ( 59 ), colorectal (CRC) ( 60 ), and breast cancer ( 61 ). Moreover, high TDO2 expression level positively correlated with higher immune infiltration, especially DCs, as well as immune checkpoint-related gene markers, such as LAIR1, CD276, NRP1, CD80, and CD86 ( 58 ). Regulation of TDO2 expression has been linked to IL-1β- C/EBPβ-MAPK signaling activities ( 62 ).…”
Section: Role Of the Kynurenine Pathway In Cancer Development And Imm...mentioning
confidence: 99%